The lived experiences of iranian patients with rheumatoid arthritis: A qualitative research - Simin Jahani; Shayesteh Haghighi; Somayeh Ansari; Elham Rajaei; Neda Sayadi (Wolters Kluwer Medknow Publications, 2022)
Background: Rheumatoid Arthritis (RA) is a chronic inflammatory disease that affects various systems of the body. The present study was conducted with the aim to explain the lived experiences of Iranian patients with RA. Materials and Methods: According to the research question, the phenomenological research approach was used. The participants were selected through purposive sampling, and sampling was continued until data saturation was achieved. The data was collected by conducting unstructured interviews and using an audio recorder. To interpret the data, an interpretive/hermeneutic approach was implemented using Van Manen's method. In addition, Lincoln and Guba's criteria were used to evaluate data robustness. Results: A total of 24 participants participated in the study. Overall, 145 basic concept codes were extracted which were classified into the four main themes of self-management with the participation of the family, spiritual resilience in the face of existing problems, the tendency to hide the disease, and the fear of an uncertain future. Conclusions: It is recommended that care providers use the findings of this study to develop care plans in the various aspects of the physical, mental, social, and spiritual needs of patients with RA based on their concerns and deep experiences. It is also suggested that other qualitative research approach methodologies such as grounded theory for explaining the process of patient care and providing an appropriate model, or action research for solving the problems of hospitalized patients through suitable care at home be implemented.